Integrating Digital Marketing Communication and Community Participation for Sustainable Tourism Development: A Case Study of Sumberbulu Tourism Village, Indonesia - Maulana, Mahesa; Deliana, Dian; Indah, Tiara (CHANNEL: Jurnal Komunikasi, 2025)
This study investigates the role of integrated digital marketing communication in enhancing visitor attraction and promoting sustainability in Sumberbulu Tourism Village, Karanganyar Regency, Central Java. Drawing on a qualitative research design, the study employs literature review, field observations, in-depth interviews, and focus group discussions with key stakeholders including village managers, local government representatives, and community members. The findings reveal that digital platforms—such as Instagram, Google Business, and Traveloka—are strategically used to promote cultural and ecological attractions. However, the digital marketing strategy faces challenges, including limited infrastructure, human resource capacity, and government support. To address these constraints, collaborative initiatives involving academic institutions and training programs have been implemented to improve digital literacy and promotional capabilities. The study also highlights the critical role of local community participation, particularly in tourism service delivery, environmental conservation, and cultural preservation. Women's involvement and community-based economic activities further reinforce the village's sustainability goals. The integration of digital technologies with community engagement and government support reflects the principles of community-based sustainable tourism (CBST). The study contributes to the academic discourse on rural tourism marketing and offers practical insights for policymakers and tourism managers aiming to enhance sustainable destination development. Future research should incorporate comparative studies across regions and include digital content creators and tourists to deepen understanding of participatory digital communication strategies in sustainable tourism.